Flotação catiônica reversa de minério de ferro usando soluções microemulsionadas e nanoemulsionadas. - Dedes, Victor Ezequiel Leite (Universidade Federal Rural do Semi-Árido, 2018)
The development of technologies and research for the separation of iron ore from the silica gangue is being driven by the drop in iron content in the deposits. By virtue of this fact, the use of faster and more advanced trading methods is obtained, receiving more good results with low operation cost. The aim of this work is to apply the Amina Flotigam EDA surfactant in a nanoemulsified system, in order to test the buoyancy of pure minerals (quartz and hematite) by means of reverse cationic flotation. A novel research line was developed in the field of mineral flotation, where the reagents used in the process, as collectors and depressants, were prepared together in a nanoemulsion, aqueous phase mixture, with and without gelatinized starch and butanol / surfactant Flotigam EDA, and an oily phase, consisting of kerosene, in a single equilibrium phase. The nanoemulsion was obtained from a microemulsion with the same components. Microflotation tests were performed on a modified Hallimond's whole, aiming to analyze the effects caused by pH variation and collector and depressant concentration, as well as to obtain a better percentage of separation of the minerals under study. The micro flotation assays used the nanoemulsion 97% of flotation for quartz and 37% for hematite using a nanoemulsion at pH 10. The results showed the feasibility of using these systems to float quartz and depress hematite.
Keywords: tensoativo; nanoemulsão; microemulsão; flotação mineral; minério de ferro; surfactant; nanoemulsion; microemulsion; mineral flotation; iron ore; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA